A novel double-stage pulsed plasma bright nitriding of spheroidal graphite (SG) cast iron. (July 2018) - Dong, Yangchun; Bell, Thomas; Li, Xiaoying; Dong, Hanshan
Abstract: To alleviate spallation and effectively hardened the spheroidal graphite cast iron, a diffusion-prevalent hardened case was produced on the spheroidal graphite iron surface by a new two-stage bright nitriding process. The unique feature of this process in treating the sharp edges with high strength and controllable layer thickness has been emphasised. An exceptionally deep diffusion layer of 300 μm was produced during bright nitriding, and the formation and thickness of the compound layer were easily controlled in this continuous short nitriding process. The produced hardened case after the first nitriding stage was mainly composed by polyphase of α/Fe4 N, in comparison to the conventional Fe2 N3 /Fe4 N of compound layer, formed along the new pearlite laminae, resulting in significantly improved surface hardness and corrosion resistance. Graphical abstract: Highlights: A method of creating a duplex hardened case with controllable compound layer for SG cast iron. The mechanism of suppressing formation during bright nitriding process has been explained. The dual-layer microstructure with transformed perlite phase is significantly corrosion resistant.